2020
DOI: 10.1002/capr.12354
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of group theraplay with refugee children in Turkey

Abstract: According to the definition of the Refugee Convention, a refugee is 'someone who is unable or unwilling to return to their country of origin, owing to a well-founded fear of being persecuted for reasons of race, religion, nationality, membership of a particular social group, or political opinion' (UN General Assembly, 1951). It is well established that refugees, including children, have high prevalence rates of mental health problems (Cayabyab, O'Reilly, Murphy, & O'Gorman, 2020). These include post-traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Similarly, Lenton (2020) reported that GT had a positive impact on behavioral difficulties in children. The result of the present study was similar to the research findings of Eruyar and Vostanis (2020), who demonstrated that the GT had a significant improvement on post-traumatic stress and attachment relationships in children. The finding of this research was similar to the research results of Orduña (2018) who revealed that GT had a significant and positive effect on the socio-emotional competence, social interactions, and pro-social behaviors of children with developmental disabilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, Lenton (2020) reported that GT had a positive impact on behavioral difficulties in children. The result of the present study was similar to the research findings of Eruyar and Vostanis (2020), who demonstrated that the GT had a significant improvement on post-traumatic stress and attachment relationships in children. The finding of this research was similar to the research results of Orduña (2018) who revealed that GT had a significant and positive effect on the socio-emotional competence, social interactions, and pro-social behaviors of children with developmental disabilities.…”
Section: Discussionsupporting
confidence: 91%
“…Lenton (2020) concluded that GT had a considerable impact on the behavioral difficulties in children who have experienced complex trauma. Eruyar and Vostanis (2020) demonstrated that the GT had a significant improvement on post-traumatic stress, mental health, and attachment relationships in children. Ray et al (2020) highlighted that children who experienced more unpleasant experiences in childhood have lower social and emotional abilities and more behavioral problems.…”
Section: Related Studymentioning
confidence: 96%
“…Such children lack a strategy to continue a secure expectation (Stauffer, 2008). They develop strong feelings of being let down and can become suspicious of strangers (Eruyar & Vosyanis, 2020). Thus, participants were trying to find a secure connection with an adult figure but appeared to feel their strategy was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…Play therapy is a psychotherapeutic approach that aims to help children explore, and express their repressed thoughts/emotions through play. A group pre-post-test study by Eruyar and Vostania (2020) assessed the effectiveness of Theraplay (a form of play therapy aimed at strengthening attachment between parents and children) in a sample of children aged 8-14 years.…”
Section: Play Therapymentioning
confidence: 99%